The Concept of Mainstream Medicine for All Californians—Part II Fifth Progress Report of the Committee on Role of Medicine in Society (1970)
This Fifth Progress Report is being printed in three parts in California Medicine. Following the appearance of Part III the report will be bound in a pamphlet which may be ordered at $1 a copy from 693 Sutter Publications, Inc., 693 Sutter Street, San Francisco, California 94102.